2021
DOI: 10.3390/agronomy11091718
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Common Wheat Grains with Combined Ca, Mg, and K through Foliar Fertilisation

Abstract: Common wheat grains are characterised by low concentrations of Ca, K, and Mg, which can be partially removed with the bran during milling processes. This preliminary study investigated the effects of foliar fertilisation at the earing stage with nitrates of Ca, Mg, and K contemporarily, together with a small amount of urea and protein hydrolysate as potential carriers, in two contrasting common wheat varieties, i.e., Solehio (medium proteins content) and Vivendo (high proteins content). Based on the preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Brennan et al (2007) reported that Ca application had a direct impact on wheat yields, which can suggest that its better uptake in Haristide could be a key factor to increase production. Indeed, Ca may modulate the absorption and translocation of several elements and maintain the integrity of selective ion transport proteins (Cobalchin et al, 2021). Lower Zn content in Haristide, irrespective of N supply, could suggest a poor root uptake or remobilization from shoots to grains (Liu et al, 2019), which is relevant for human diet to avoid symptoms, such as loss of appetite, growth retardation, rough and peeling skin, and immune system dysfunction (Wang et al, 2020).…”
Section: N Fertilization Has a Significant Effect On Grain Yield And ...mentioning
confidence: 99%
“…Brennan et al (2007) reported that Ca application had a direct impact on wheat yields, which can suggest that its better uptake in Haristide could be a key factor to increase production. Indeed, Ca may modulate the absorption and translocation of several elements and maintain the integrity of selective ion transport proteins (Cobalchin et al, 2021). Lower Zn content in Haristide, irrespective of N supply, could suggest a poor root uptake or remobilization from shoots to grains (Liu et al, 2019), which is relevant for human diet to avoid symptoms, such as loss of appetite, growth retardation, rough and peeling skin, and immune system dysfunction (Wang et al, 2020).…”
Section: N Fertilization Has a Significant Effect On Grain Yield And ...mentioning
confidence: 99%
“…In general, it is important to indicate that the protein, lipid, and ash contents in the end products depend on the specific type of algae utilised and the conditions under which they are cultivated. In general, wheat grains typically contain low concentrations of calcium (Ca), potassium (K), and magnesium (Mg), which can be partially removed with the bran during the milling processes [60]. The addition of microalgae biomass can enhance these mineral contents, which are essential for bone health, nerve function, and maintaining overall wellbeing.…”
Section: Nutritive Valuementioning
confidence: 99%
“…Brennan et al (2007) reported that Ca application had a direct impact on wheat yields, what can suggest that its better uptake in Haristide could be a key factor to increase production. Indeed, Ca may modulate the absorption and translocation of several elements and maintain the integrity of selective ion transport proteins (Cobalchin et al, 2021). Lower Zn content in Haristide, irrespective of N supply, could suggest a poor root uptake or remobilisation from shoot to grains (Liu et al, 2019), which is relevant for human diet to avoid symptoms such as loss of appetite, growth retardation, rough and peeling skin, and immune system dysfunction (Wang et al, 2020).…”
Section: Phenotyping Approaches To Assess the Effect Of N And Genotyp...mentioning
confidence: 99%